Pengaruh Metode Pembelajaran Teka Teki Silang (TTS) Terhadap Hasil Belajar Pada Tema 8 Subtema 1 Siswa Kelas V SDN Rejoslamet 2 Jombang - Nur Alfi Laili; Isna Ida Mardiyana (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to determine whether there is a significant influence of the Crossword Puzzle (TTS) learning method on student learning outcomes on theme 8 sub-themes 1 of class V Elementary School Rejoslamet 2 Jombang. This research is a quantitative research type of experimental research, the design used is Pre-Experimental Designs. The population of this study were all fifth grade students at Rejoslamet 2 Jombang Elementary School. Sampling using non-probability sampling using saturated sampling technique, the number of samples is all students of class V Elementary School Rejoslamet 2 Jombang totaling 39 students. Data were collected using observation and tests, analysis of instrument data using content validity and construct validity tests, reliability tests, item difficulty level tests, and differential power tests, while statistical analysis used normality tests. Test the hypothesis in this study using a paired sample t-test. The results of the research hypothesis test are the significance value (2-tailed) < value (0.05), namely 0.000 < 0.05 and decision making through the results of the t test with the decision-making rule - t count < -t table, where -t count namely -13, 403 < -table, namely -1,686 or t count (-13,403) < t table (1,686) means that Ha is accepted and H0 is rejected or there is a significant influence of the application of the crossword puzzle method on learning outcomes in theme 8, sub-theme 1 student class V Elementary School Rejoslamet 2 Jombang, then H0 is rejected and Ha is accepted, which means that there is a significant influence of the application of the crossword puzzle learning method on learning outcomes in theme 8 sub-theme 1 students of class V Elementary School Rejoslamet 2 Jombang.